Some Principled Aspects of a New Law - Guerra, Luis Felipe (1969)
The article addresses a change in the evolution of law from a philosophical perspective. For the author, the immutable conception of Law has been losing strength to give way to a dynamic and no longer absolute interpretation; and the fact is that Law is intimately linked to man, which has been changing in recent times. This situation has generated a conflict, since it is not possible to frame the human being in an immutable juridical structure. For this reason, countless efforts have been made to address this problem. In this context, the author divides the attempts that legal scholars have made to solve this problem into three groups, classifying them as follows: i) logical-scientific foundation, ii) legal conventionalism and iii) practicality. Finally, the author concludes by pointing out that legal research must be oriented towards a conception of man, given that the new law is based on principles that manifest human relations that are variable and interactive.